1998
DOI: 10.1016/s0167-4889(98)00144-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into structure and function of MRP8 (S100A8) and MRP14 (S100A9)

Abstract: The two migration inhibitory factor- (MIF)-related protein-8 (MRP8; S100A8) and MRP14 (S100A9) are two calcium-binding proteins of the S100 family. These proteins are expressed during myeloid differentiation, are abundant in granulocytes and monocytes, and form a heterodimeric complex in a Ca2+-dependent manner. Phagocytes expressing MRP8 and MRP14 belong to the early infiltrating cells and dominate acute inflammatory lesions. In addition, elevated serum levels of MRP8 and MRP14 have been found in patients suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
233
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(244 citation statements)
references
References 72 publications
6
233
0
2
Order By: Relevance
“…In squamous cell carcinomas, these closely interacting proteins may be viewed primarily in the context of altered Ca-dependent gene expression resulting in inhibited or retarded differentiation and, in particular, in loss of proapoptotic activity. In the neutrophils, the abundantly expressed calgranulins show strong proinflammatory activity similar to the defensins (Kerkhoff et al, 1998). Intriguingly, our IHC studies confirmed the extensive reduction in calgranulin levels in the tumors and surrounding epithelia, but at the same time showed retained or even enhanced calgranulin levels in stromal neutrophils (Roesch Ely et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…In squamous cell carcinomas, these closely interacting proteins may be viewed primarily in the context of altered Ca-dependent gene expression resulting in inhibited or retarded differentiation and, in particular, in loss of proapoptotic activity. In the neutrophils, the abundantly expressed calgranulins show strong proinflammatory activity similar to the defensins (Kerkhoff et al, 1998). Intriguingly, our IHC studies confirmed the extensive reduction in calgranulin levels in the tumors and surrounding epithelia, but at the same time showed retained or even enhanced calgranulin levels in stromal neutrophils (Roesch Ely et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…In cells, MRP-14 is predominantly found in a heterodimeric complex with MRP-8 (26,27). To assess the ability of p38 MAPK to phosphorylate MRP-14 while complexed with MRP-8, MRP-14/MRP-8 complexes were purified from human neutrophils under nondenaturing conditions.…”
Section: In Vitro Phosphorylation Of Mrp-14 By P38 Mapkmentioning
confidence: 99%
“…One of the proteins identified was myeloid-related protein-14 (MRP-14), a member of the S100 protein family of calcium binding proteins (24,25). MRP-14 and its binding partner, MRP-8, are highly expressed in neutrophils and monocytes, comprising up to 30% of the total cytosolic protein mass in neutrophils (26,27). In addition to the unmodified protein of 114 amino acids, an isoform with deletion of the N-terminal four amino acids (MRP-14*) also exists (24 -27).…”
mentioning
confidence: 99%
“…[1] Recent studies have showed that S100A8 has been implicated in the pathobiology of inflammatory disorders, such as asthma, rheumatoid arthritis, and inflammatory bowel disease. [2] It is well known that the inflammatory and immune reactions are involved in cerebral ischemia reperfusion (I/R),[3,4] but whether S100A8 mediates the injury in the process of cerebral I/R is still unknown.…”
Section: Introductionmentioning
confidence: 99%